SUPERVISI PENGAWAS PENDIDIKAN AGAMA ISLAM DI SD NEGERI 002 KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR TAHUN 2021 - Suhambia (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
This study suggests the implementation of supervision by the supervisor of Islamic education at SDN 002 Kuntu and what factors influence the supervisor of Islamic education in carrying out supervision at SDN 002 Kuntu.This study aims to determine the implementation of supervision by Islamic Religious Education Supervisors at SDN 002 Kuntu and the factors that influence Islamic Religious Education Supervisors in carrying out such supervision.The subjects in this study were supervisors of Islamic Religious Education in Kampar Kiri District in 2009 with one supervisor. While the object of this research is about the Implementation of Supervision by Islamic Religious Education Supervisors at SDN 002 Kuntu, amounting to 2 units, namely SDN 002 Kuntu, and SDN 006 Kuntu,Data collection in this study used observation, interviews, and documentary techniques, then editing, classification, and conclusion were used for data processing. Then the data is presented and analyzed descriptively qualitatively and concluded by using the inductive method.The results of this study indicate that the implementation of supervision by the Islamic Religious Education Supervisor at SDN 002 Kuntu has been quite carried out in accordance with the tasks assigned. This is supported by internal and external factors, namely education and experience, age and health, competence and skills, and external factors, namely environment and territory, supervision, funds and facilities